Student Support and Guidance Services in Australian Higher Education: A Cross-Institutional Analysis of Career Counseling and Academic Development Programs - Septien Dwi Savandha; Adelia Azzahra; Alifa Suri Rahmadhina (P3M STAI Kuningan, 2025)
Background: Student support services play critical roles in facilitating academic success and career development within higher education, yet a comprehensive understanding of their organisational structures, delivery models, and effectiveness across Australian institutions remains limited.Objective: This study systematically examined career counselling and academic development services across diverse Australian universities to identify factors associated with effective, accessible, and equitable service provision.Method: A convergent parallel mixed-methods design was employed across 22 institutions, integrating institutional questionnaires, surveys of 118 staff members and 4,847 students, semi-structured interviews, focus groups, and document analysis conducted over 18 months.Findings and Implications: Results revealed substantial heterogeneity in organisational structures, with student-to-staff ratios averaging 3,426:1 for career services and 2,673:1 for academic development. Appointment wait times (35.8%) and lack of service awareness (24.3%) emerged as primary barriers, while institutional factors including staffing ratios, operating hours, and delivery modalities explained 47.6% of variance in student satisfaction. International students and female students utilised services at significantly higher rates.Conclusion: Findings provide an evidence-based foundation for enhancing service accessibility, adequacy, and equity through organisational innovations, capacity enhancement, extended operating hours, and culturally responsive programming, with implications for institutional policy and sector-wide quality assurance frameworks.